The religious position of Darul Arqam and Shi'ites in Selangor from the perspective of Jabatan Agama Islam Selangor (JAIS) - Nurul Shuhaida binti Mohd Salleh (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
The present research is an attempt to explicate the Jabatan Agama Islam (JAIS)'s perspective regarding the religious position of the Darul Arqam and the Shi'ites in Selangor. As the responsible body in quelling the deviant believes and practices in Selangor, the JAIS had issued the fatwa on these movements and listed few of their characteristics. This study attempts at examining the perspective of the JAIS on the teaching of these two movements which contradicts the opinion of Ahl al-Sunnah wal-Jama'ah. The methodology applied in this study is the textual analysis and obtaining the views from the JAIS through interviews. This study highlighted several characteristics and the fatwa issued by the JAIS on the teaching of the Darul Arqam and the teaching of Shi'ites which affirmed to be dangerous practices that could threaten the 'aqidah of Muslims in Selangor. This study stresses that both of the deviant teachings are considered to be deviant groups and that teachings strayed from the real Islamic teachings in Selangor because both teachings contradict with the teaching of Ahl al-Sunnah wa l-Jama'ah. Finally, this study concludes that it is crucial for Muslim in Selangor to have comprehensive knowledge about Islam. This proper knowledge would guide them to practice the teaching of Islam as practiced by the Ahl al-Sunnah wa l-Jama'ah and become the true believers of Islam.